1999
DOI: 10.1680/gein.6.0153
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Geosynthetic Interaction - Influence of Soil Particle Size and Geosynthetic Structure

Abstract: This paper reports the results of pullout tests on five different geosynthetics embedded in two different granular soils. Soil and geosynthetic properties are described and soil-geosynthetic interaction behaviour is studied. Based on the results of pullout tests, the influence of soil particle size, geosynthetic structure, and the role of geogrid bearing members are discussed. The main conclusion is that the influence of soil particle size on soil-geosynthetic interaction is important, but its significance dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…For the interface between sands and extensible materials, such as extruded geogrids, factor F1 (Equation 4) was found too optimistic (Lopes and Lopes 1999b). Lopes and Lopes (1999a) reported contributions of the bearing members of extruded geogrids for the pullout strength confined in two different sands of ~ 26%.…”
Section: Coefficient Of Interaction In Pulloutmentioning
confidence: 99%
See 1 more Smart Citation
“…For the interface between sands and extensible materials, such as extruded geogrids, factor F1 (Equation 4) was found too optimistic (Lopes and Lopes 1999b). Lopes and Lopes (1999a) reported contributions of the bearing members of extruded geogrids for the pullout strength confined in two different sands of ~ 26%.…”
Section: Coefficient Of Interaction In Pulloutmentioning
confidence: 99%
“…The behaviour of the soil-geosynthetic interface in pullout depends on: particle size distribution and density of the soil; structure of the geosynthetic; ratio between the geogrid apertures and the soil grain sizes, when relevant Ladeira 1996, Lopes andLopes 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the shear strength parameters obtained from the large-scale direct shear were found to be smaller than the results of the triaxial UU tests. Lopes and Lopes (1999) [12] investigated the influence of particle size of the soil and geosythetic structure. They concluded that an increase in soil-geogrid interface shear resistance is observed when the soil contained a significant percentage of particles with sizes slightly greater than the thickness of the geogrid bearing members, but smaller than the geogrid apertures.…”
Section: Introductionmentioning
confidence: 99%
“…Jewell 1980;Palmeira and Milligan 1989;Lopes and Ladeira 1996;Sobhi and Wu 1996;Lopes and Lopes 1999;Perkins and Cuelho 1999;Sugimoto et al 2001;Palmeira 2004;Moraci and Recalcati 2006). The soil-geogrid interaction mechanism has been investigated using full-scale tests, model tests, and numerical analyses.…”
Section: Introductionmentioning
confidence: 99%